Arterial Stiffness in a Toddler with Neurofibromatosis Type 1 and Refractory Hypertension - Stella Stabouli; Euthymia Vargiami; Olga Maliachova; Nikoleta Printza; John Dotis; Maria Kyriazi; Konstantinos O. Papazoglou; Dimitrios Zafeiriou (Case Reports in Pediatrics)
Arterial hypertension is a common finding in patients with neurofibromatosis (NF) type 1. Renovascular hypertension due to renal artery stenosis or midaortic syndrome could be the underlying cause. We report the case of a 4-year-old girl with NF type 1 and midaortic syndrome whose changes in blood pressure and pulse wave velocity suggested the evolution of vasculopathy, diagnosis of renovascular hypertension, and provided insights of response to treatment. Hypertension persisted after percutaneous transluminal angioplasty in the abdominal aorta, requiring escalation of antihypertensive treatment, while arterial stiffness demonstrated a mild decrease. Regular assessment of blood pressure using ambulatory blood pressure monitoring and noninvasive assessment of arterial stiffness may enhance the medical care of patients with NF type 1.